Mandatory pension funds in Chile: Decline of the arrangement? - Anna Ząbkowicz (e-Finanse: Financial Internet Quarterly, 2017)
Chile has been both a pioneer and the most radical follower of the idea of converting pension savings into contributions to privately-managed capital funds. Two recent portions of reforms under President Bachelet extended the social safety net as well as re-introduced publicly-administered programs on behalf of retirees. Does such direction, in the country with the longest lasting evidence of privatized fully-funded pensions mean a fall of the arrangement? The article attempts a political-economic argumentation in aim to form the answer. The premise is that risk sharing constitutes a crucial issue in insurance industry where old-age security is largely placed. In social security segment the risk of default on liabilities is backed by taxing capacity of the state; in fully-funded-pensions plans normally this is individual contributor who faces the portfolio risk. Therefore change in risk sharing between the contributors to the funds, pension management companies and the state is fundamental for evaluation of the reforms. The review of Chilean reforms reveals an institutional arrangement which is fundamental to risk sharing, namely the relation between contribution and benefit, left intact. This finding supports the conclusion that bringing recently the state back into retirement system can not be conceived as any systemic revolution.
Keywords: P16; B52; 330; the political economy of pension reforms; funded pensions; risk sharing